Analysis of virulence genes sequencing of Serratia marcescens in iraqi hospitals: Genes sequencing of Serratia marcescens - Salim Hamzah, Alaa; Sami Awayid, Hussam (Cellular and Molecular Biology, 2023)
Analysis of virulence genes (PhlA, ShlA, FlhD) sequencing of Serratia marcescens including collection of two hundred twenty samples from sputum & wound infection of the period from April-June in 2021 of the patients in some hospitals in Baghdad – Iraq. These specimens were collected from central hospitals in Iraq. After laboratory diagnosis of these specimens by detecting morphological and biochemical tests on bacteria that were cultured on selective and enriched media, VITEK- 2 compact system. There are 40 bacterial isolates of Serratia marcescens from total samples (220) in percentage (18.18%). The genome of these bacteria was extracted to investigate target virulence genes that were amplified by specific forward and specific primers. The product size of virulence genes was Ph1A (207 bp), Sh1A (217 bp), and FlhD virulence gene (307 bp). The results exhibited that these isolates contained these genes at different levels. Sequencing of these genes was carried out and analyzed through BLAST in NCBI and Geneious version -9. The results explained the top identity of sequencing these virulence genes (PhlA, ShlA, FlhD) between local Iraqi bacteria. In addition, there are misidentify or dissimilarities in different levels between Iraqi S. marcescens and global strain recorded in NCBI. These results consider scientific evidence to find new variations of these virulence genes in Iraqi S. marcescens in comparison with the global strain. These new Iraqi bacterial variation sequencing registered in the global database in NCBI under accession numbers including (Ph1A virulence gene LC647828.1 & LC647829.1), (Sh1A virulence gene LC647830.1 & LC647831.1) & (F1hD virulence gene LC647826.1, LC647827.1). The results of analysis sequencing exhibited different percentages in genetic identity distance, which refer to these bacteria new variation in Pathogenicity Island. These results explained the ability of these bacteria to produce different levels of virulence factors that lead to an increase in pathogenicity and spreading of infection.